Handbook of sustainable development planning: Studies in modelling and decision support, second edition - Quaddus, Mohammed; Siddique, M. (2013)
© M.A. Quaddus and M.A.B. Siddique 2013. All rights reserved. The thoroughly revised second edition of this authoritative Handbook, complete with new chapters, comprehensively examines the current status and future directions of model-based systems in decision support and their application to sustainable development planning.